KARAKTERISTIK CAMPURAN ASPAL PORUS DENGAN BAHAN TAMBAH TAFPACK-SUPER - Mita Suryani, Fitrika
THE CHARACTERISTICS OF POROUS ASPHALT MIXTURE WITH ADDITIVE TAFPACK-SUPER, Fitrika Mita Suryani, 2002. Transportation Engineering, Magister Program of Civil Engineering, Institute of Technology Bandung. Porous asphalt is a bituminous mix with low sand content to achieve a high air voids content. It is promoted as being effective in enhancing traffic safety in rainy weather, reducing hydroplaning tendencies, and as having good skid resistance properties at higher speeds. In this research, asphalt porous mixture were designed by adding TAFPACKSuper 0%, 12% and 15%. Unconditioned Cantabro Loss Test are 8,89% to 19,91%. Adding TAFPACK-Super about 12% and 15% decrease the Cantabro Loss values about 3,53% to 11,07% and 2,40% to 9,41%. It means that the number of loss particle using Los Angeles Abrasion Machine Test are decreased with adding TAFPACK-Super. Conditioned Cantabro Loss Test also have tendency decreased with adding TAFPACK-Super 22,80%, 12,89% and 9,9% in adding TAFPACK-Super 0%, 12% and 15%. Asphalt Flow Down Test also shows decreased tendency of amount bituminous that run off with adding TAFPACK-Super 0,15% to 0,29% for 0%, 0,07% to 0,20% for 12% and 0,06% to 0,19% for adding TAFPACK-Super 15%. Mixtures at optimum binder content (OBC) were tested by Marshall Immersion Test and Conditioned Cantabro Loss Test. OBC for 0% TAFPACK-Super is found 5,1% by Australian method and 5,5% by Japanese method. For adding 12% TAFPACKP-Super OBC is found 5,3% by Australian method and 5,5% by Japanese method and for 15% TAFPACK-Super OBC is found 5,6% by Australian method and 5,5% by Japanese method. In fact, the Marshall method could not be implemented in this case and the OBC could not be determined because the stability was less than the minimum specified (500 kg) and the VIM value was more than VIM specified (3% - 5%)